2014
DOI: 10.1073/pnas.1402105111
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence that Celsr3 and Celsr2 , together with Fzd3 , regulate forebrain wiring in a Vangl -independent manner

Abstract: Celsr3 and Fzd3, members of "core planar cell polarity" (PCP) genes, were shown previously to control forebrain axon guidance and wiring by acting in axons and/or guidepost cells. Here, we show that Celsr2 acts redundantly with Celsr3, and that their combined mutation mimics that of Fzd3. The phenotypes generated upon inactivation of Fzd3 in different forebrain compartments are similar to those in conditional Celsr2-3 mutants, indicating that Fzd3 and Celsr2-3 act in the same population of cells. Inactivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 78 publications
2
57
0
Order By: Relevance
“…However, mutations in Vangl2 and Dact1 that exhibit strong mutual rescue during gastrulation [13] do not exhibit similar reciprocal functional relationships during neurodevelopment, suggesting that the molecular mechanisms underlying these phenotypes differ. Consistent with other studies [15,38,39] our genetic work therefore suggests that although components of the PCP pathway play important roles in the nervous system, the molecular pathways by which they function in developing neurons differ substantially from the PCP pathway established in studies of basic embryonic development. …”
Section: Resultssupporting
confidence: 90%
“…However, mutations in Vangl2 and Dact1 that exhibit strong mutual rescue during gastrulation [13] do not exhibit similar reciprocal functional relationships during neurodevelopment, suggesting that the molecular mechanisms underlying these phenotypes differ. Consistent with other studies [15,38,39] our genetic work therefore suggests that although components of the PCP pathway play important roles in the nervous system, the molecular pathways by which they function in developing neurons differ substantially from the PCP pathway established in studies of basic embryonic development. …”
Section: Resultssupporting
confidence: 90%
“…That ADGRCs (CELSRs) influence neuronal cell adhesion is apparent from studies of axon guidance in insects (Chen and Clandinin, 2008). In distinct organisms, ADGRCs (CELSRs) differentially interact, either genetically or directly, with various proteins, such as Frizzled, Gogo, Espinas, Vangl2, and RhoA, to control axon outgrowth and targeting, as well as dendritic self-avoidance (BergerMuller and Suzuki, 2011;Matsubara et al, 2011;Hakeda and Suzuki, 2013;Huarcaya Najarro and Ackley, 2013;Chai et al, 2014;Qu et al, 2014). These studies give credence to the idea that the function of 7TM-cadherins could be defined by their binding partners in cis (Berger-Muller and Suzuki, 2011).…”
Section: Skeletal Muscle and Bonementioning
confidence: 99%
“…Loss of either Fzd3 or Celsr3 in the mouse results in loss of the major axon tracts that connect the thalamus and the cortex, and failure of commissural neurons in the spinal cord to project anteriorly following midline crossing (Chai et al, 2015). Because the axon guidance defects observed in some PCP mutants are not detected in others, it has been suggested that core PCP components function independently of one another in some guidance events (Qu et al, 2014). Here, we focus on spinal commissural axon guidance in mammals, where components of both the Fzd and Vangl complexes have been implicated, and in which live imaging of PCP protein localization during guidance decisions has provided mechanistic insights.…”
Section: Pcp Signaling During Axon Guidancementioning
confidence: 99%